Phylogenetic Analysis Of Endophytic Fungi Isolate from Bellucia pentamera Naudin Based On ITS rDNA - Andika Puspita Dewi; Elisa Nurnawati; Laila Hanum; Hary Widjajanti (Indonesian Journal of Environmental Management and Sustainability, 2019)
Endophytic fungi can produce secondary metabolites of endophytic fungi isolated from host plants. The purpose of this study is to identify and analyze the sequencing of endophytic fungi isolates with ITS and Beta-tubulin markers and phylogenetic trees. The endophytic fungi isolate DKJ1, DKJ3a, DKJ3c and DKJ4 were successfully isolated from the cardia plant (Bellucia pentamera Naudin) indicated by Aspergillus niger group, Aspergillus fumigatus group and Penicillium sp. The results of the sequencing analysis of isolates DKJ1, DKJ3a, DKJ3c, and DKJ4 were successfully amplified with an annealing temperature of 54ºC with a pair of ITS1-ITS4 primers with a molecular weight of 570 bp and a Beta-Tubulin primer with an annealing temperature of 56.1ºC molecular weight of 550 bp. From the results of identification and analysis of DNA sequencing of endophytic fungi DKJ1, DKJ3a, DKJ3c and DKJ4 with the primary pair of ITS and Beta-tubulin shows that the phylogenetic tree is different from the species obtained. ITS DKJ1 isolates have similarities with the species Aspergillus piperis CBS 112811, ITS DKJ3c has similarities with the species Aspergillus flavus var flavus strain ATCC 16833, ITS DKJ3a has similarities with Penicillium rolfsii strain NRRL 1078 species and ITS DKJ4 has similarities with Penicillium oxalicum NRRL 787 species. Whereas isolate from DKJ1 Beta-Tubulin has similarities with NRRL 4875 Aspergillus tubingensis species, DKJ3c has similarities with species of Aspergillus novoparasiticus strain DTO 223-C4 and DKJ4 has a similarity with Penicillium guaibinensis species. But there are similarities based on Cluster A (Aspergillus Group) and Cluster B (Penicillium Group) on phylogenetic trees.